PENGARUH MOTIF BELANJA HEDONIC DAN MOTIF BELANJA UTILITARIAN TERHADAP KEPUASAN - Yuwono, Sapta Bagas Putra; Maduwinarti, Ayun; Mulyati, Diana Juni (Jurnal Dinamika Administrasi Bisnis, 2018)
This research entitled "The Influence of Hedonic Shopping Motif and Utilitarian Utility Motivation on Consumer Satisfaction (Case Study at Carrefour BG Jungtion Surabaya)". This study aims to determine the effect of Hedonic Motifs and Utilitarian Motives Against customer satisfaction in Carrefour BG Jungtion Surabaya. The population in this study are consumers who are shopping at Carrefour Surabaya, aged minimum 18 th, samples taken as many as 100 respondents. The variables used are Hedonic Motives and Utilitarian Motives and consumer satisfaction. Method of data collection using questionnaire method by using technique of Non Probability Sampling that is incidental sampling. The data obtained in the analysis using multiple linear regression analysis is processed with the help of SPSS program application. The results obtained conclusion as follows: 1. There is a positive influence of Hedonic Motives on Customer Satisfaction Partial test results have a significance level value of (<0,05), 2). Based on the results of research, partially Utilitarian Motive variable No effect on customer satisfaction with a significance value of (>0,05), 3). Hedonic Motives and Utilitarian Motives are jointly influential and accepted to customer satisfaction, Simultaneous test results (F) are obtained with a <0.000 significance level.Â Keywords: Hedonic Motives, Utilitarian Motives and Consumer Satisfaction